Evidence that dog ownership protects against the onset of disability in an older community-dwelling Japanese population. - Yu Taniguchi; Satoshi Seino; Bruce Headey; Toshiki Hata; Tomoko Ikeuchi; Takumi Abe; Shoji Shinkai; Akihiko Kitamura (PLoS ONE)
Objectives This study examined the association between dog and cat ownership, the onset of disability and all-cause mortality in an older population. Dog and cat owners take more regular exercise and have closer social relationships than non-owners. We further assess the beneficial effects of these moderating variables on the onset of disability and mortality. Methods Dog and cat ownership data were collected from 11233 community-dwelling adults age 65 years and older. These data were matched with data about the onset of disability held by the Japanese long-term care insurance system. Local registry data were used to ascertain all-cause mortality. Results During the approximately 3.5 year follow-up period, 17.1% of the sample suffered onset of disability, and 5.2% died. Logistic regression analysis indicated that, compared with a reference group of those who had never owned a dog (odds ratio fixed at 1.0), older adults who were currently dog owners had a significantly lower odds ratio of onset of disability (OR = 0.54 95% CI: 0.37-0.79). Our results further show that regular exercise interacts with dog ownership to reduce the risk of disability. The association of dog and/or cat ownership with all-cause mortality was not statistically significant. Conclusions Dog ownership appears to protect against incident disability among older Japanese adults. Additional benefits are gained from ownership combined with regular exercise. Daily dog care may have an important role to play in health promotion and successful aging.